Enhancing Access to Affordable Housing Through the Improved Mechanical and Durability Properties of Mud-Crete Blocks - Akeke, G. A.; Ewa, D. E.; Takim, S. A.; Enang, A. E (European Journal of Applied Sciences, 2024)
The results of an experimental study using cement, rice husk ash (RHA), sand, and laterite as constituents to create solid mud-Crete blocks' mechanical and durability characteristics are presented in this work. RHA and laterite partially replaced cement and sand respectively in percentages of 10, 20 and 30%. Grade 32.5 Portland Limestone Superset cement was used and the experimental procedure carried out on the blocks included compressive strength, water absorption and fire resistance tests. Curing was by sprinkling and the results showed that at 7 days curing time the average compressive strengths recorded were 2.97N/mm2 for the control mix, and 2.65N/mm2, 1.72N/mm2 and 1.09N/mm2 for 10, 20 and 30% replacements, and after 28 days curing 3.01N/mm2, 2.92 N/mm2 1.93N/mm2 and 1.31N/mm2. 7.12%, 8.10%, 8.52% and 8.78% were recorded as average values for water absorption after 28 days of curing for the control mix and the replacements at 10, 20 and 30% respectively. The fire resistance test showed that the specimen had integrity for 8hrs, 6hrs 18mins, 5hrs 6mins and 3hrs 19mins approximately for the control batch, 10%, 20% and 30% replacements respectively.